(Z)-3-(3,4-Dimethoxybenzylidene)-2,3-dihydro-1,5-benzothiazepin-4(5H)-one - M. Bakthadoss; R. Selvakumar; N. Manikandan; S. Murugavel (Acta Crystallographica Section E, 2013)
In the title compound, C18H17NO3S, the seven-membered thiazepine ring adopts a slightly distorted sofa conformation. The dihedral angle between the mean plane of the benzothiazepine ring system and the benzene ring is 5.9 (1)°. The molecular conformation is stabilized by an intramolecular C—H...S hydrogen bond, which generates an S(7) ring motif. In the crystal, N—H...O and C—H...O hydrogen bonds link inversion-related molecules into dimers, incorporating R12(6) and R22(8) ring motifs; the acceptor O atom is bifurcated. These dimers are further linked by C—H...O hydrogen bonds, forming supramolecular tapes running along the a axis. These are connected into the three-dimensional architecture by C—H...π interactions.